Physicochemical and Microbiological Properties of Different Kayseri Pastirma Types - Cansu Ceviker; Cansu Karakose; Gizem Kahraman; Nagihan Aydin; İsmet Öztürk (International Journal of Gastronomy Research, 2025)
In this study, a total of 20 pastirma samples were collected from the Kayseri local market, and their physicochemical (moisture, pH) and microbiological (lactic acid bacteria, total yeast-mold, total mesophilic aerobic bacteria) properties were investigated. Moisture and pH values of samples ranged from 34.77 to 57.61% and 5.81 to 6.22, respectively. While LAB counts of samples ranged from <2 to 5.61 log CFU/g, TMAB counts were found between 3.89 and 8.60 log CFU/g. Yeast counts were highest in the P9 sample, while mold counts were highest in the P11 sample. In conclusion, these pastirma samples exhibited significant variability in the physicochemical and microbiological properties due to differences in sample type and production conditions. Furthermore, the use of different culture media led to variations in yeast and mold counts, highlighting the critical role of media selection in accurately assessing the microbiological characteristics of pastirma.